Kuwait : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Improved terms of trade and sound macroeconomic policies have helped strengthen Kuwait's financial situation. The government should move forcefully to implement its structural reform program. Monetary policy is rightly focused on maintaining the credibility of the pegged exchange rate arrangement and achieving price stability. The pegged exchange arrangement, open capital account, and prudent fiscal and monetary policies have served Kuwait well, keeping inflation low and reinforcing confidence in the economy. The government has been commended for maintaining a generous foreign assistance program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet